Moralitas Perang dan Pembangunan Perdamaian dalam Perspektif Teologi Dogmatik: Refleksi Kontekstual atas Konflik Sosial Kontemporer - Bonifasius (Teokristi: Jurnal Teologi Kontekstual dan Pelayanan Kristiani, 2026)
Armed conflict and social violence remain persistent throughout human history, posing complex moral challenges for Christian theology. In this context, dogmatic theology plays a crucial role in reinterpreting the teachings of the Christian faith regarding the morality of war and the pursuit of peace. This article aims to analyze the moral status of war within the perspective of Catholic theology and to explore the possibilities for peacebuilding in situations of conflicting interests. This study employs a qualitative literature-based approach, analyzing Church documents, works of systematic theology, and articles from relevant national and international theological journals. The findings indicate that the Christian theological tradition acknowledges the legitimacy of self-defense under certain circumstances through the concept of Just War Theory, while consistently affirming that peace remains the ultimate goal of human life and the moral vocation of the Church. In Catholic theology, peace is understood not merely as the absence of war, but as a process of reconciliation that involves social justice, the restoration of relationships, and respect for the dignity of every person created in the image of God. In the context of pluralistic societies such as Indonesia, peacebuilding also requires a dialogical approach that promotes interreligious cooperation, social solidarity, and a shared commitment to justice and the common good.